Mata30 TT1 2012F
Mata30 TT1 2012F
Mata30 TT1 2012F
x 3
(a) [ 2 marks] Find the domain and range of f.
Solution:
The domain of f is R.
The range of f is R.
(b) [ 1 mark] Show that f is invertible.
Solution:
If x
1
= x
2
, then x
1
3 = x
2
3 and therefore
3
x
1
3 =
3
x
2
3. This shows
that f is one to one and therefore invertible.
Or: by using the horizontal line test on the graph of f below, we see that no
horizontal line crosses the graph of f more than once, so f is one to one and
therefore invertible.
-5 -4 -3 -2 -1 0 1 2 3 4 5
-5
-4
-3
-2
-1
1
2
3
4
5
(c) [ 3 marks] Find f
1
, the inverse of f, and give its domain and range.
Solution:
Let y =
3
x 3. Then:
y
3
= x 3
y
3
+ 3 = x
Switching x and y we get that the inverse function y = f
1
is given by y = x
3
+3.
The domain of f
1
is the range of f which is R.
The range of f
1
is the doman of f which is R.
(d) [ 4 marks] Give the graphs of f and f
1
.
-5 -4 -3 -2 -1 0 1 2 3 4 5
-5
-4
-3
-2
-1
1
2
3
4
5
MATA30F page 2
2. (a) [ 4 marks] If sec =
9x
3
for
3
2
, 2
81x
2
9
9x
cot x =
3
81x
2
9
Since
3
2
, 2
1 + x
1 x
Solution:
lim
x0
x
1 + x
1 x
= lim
x0
x
(
1 + x
1 x)
1 + x +
1 x)
(
1 + x +
1 x)
= lim
x0
x(
1 + x +
1 x)
(1 + x (1 x))
= lim
x0
x(
1 + x +
1 x)
2x
= lim
x0
(
1 + x +
1 x)
2
=
(
1 +
1)
2
= 1
(c) lim
x4
2x +|2x|
x +|x|
.
Solution:
lim
x4
2x +|2x|
x +|x|
=
2 4 +|2 4|
4 +|4|
=
16
8
= 2
MATA30F page 4
(d) lim
x
e
x
cos(x +
1
x
)
Solution: Since for all x R,
1 cos x 1,
then for all x = 0:
1 cos(x +
1
x
) 1
e
x
e
x
cos(x +
1
x
) e
x
.
Since lim
x
e
x
= 0 and lim
x
e
x
= 0,
lim
x
e
x
cos(x +
1
x
) = 0 by the squeeze theorem.
(e) lim
x1
tan(x 1)
2x 2
Solution:
lim
x1
tan(x 1)
2x 2
= lim
x1
sin(x 1)
cos(x 1)(2x 2)
= lim
x1
sin(x 1)
(x 1)
1
2 cos(x 1)
=
1
2
MATA30F page 5
4. [5 marks] Let f(x) =
(x
2
9)(x
2
4)
(x
4
x
3
6x
2
)
. Find all the horizontal and vertical asymp-
totes of f. Justify your answer by using appropriate limits.
Solution:
For horizontal asymptotes:
lim
x
(x
2
9)(x
2
4)
(x
4
x
3
6x
2
)
= lim
x
(x
4
13x
2
+ 36)
(x
4
x
3
6x
2
)
= lim
x
x
4
x
4
13x
2
x
4
+
36
x
4
x
4
x
4
x
3
x
4
6x
2
x
4
= lim
x
1
13
x
2
+
36
x
4
1
1
x
6
x
2
= 1
lim
x
(x
2
9)(x
2
4)
(x
4
x
3
6x
2
)
= lim
x
(x
4
13x
2
+ 36)
(x
4
x
3
6x
2
)
= lim
x
x
4
x
4
13x
2
x
4
+
36
x
4
x
4
x
4
x
3
x
4
6x
2
x
4
= lim
x
1
13
x
2
+
36
x
4
1
1
x
6
x
2
= 1
Thus there is one horizontal asymptote, y = 1.
For vertical asymptotes we rst simplify by factoring the function as much as possible:
f(x) =
(x
2
9)(x
2
4)
(x
4
x
3
6x
2
)
=
(x 3)(x + 3)(x 2)(x + 2)
x
2
(x
2
x 6)
=
(x 3)(x + 3)(x 2)(x + 2)
x
2
(x 3)(x + 2)
So
f(x) =
(x + 3)(x 2)
x
2
for all x R, x / {2, 0, 3}
Thus:
lim
x2
(x + 3)(x 2)
x
2
=
4
4
= 1
lim
x3
(x + 3)(x 2)
x
2
=
6
9
=
2
3
lim
x0
f(x) = lim
x0
(x + 3)(x 2)
x
2
=
(as x 0 (x + 3)(x 2) 3(2) = 6 < 0 the denominator x
2
0
+
.)
This shows that f has one vertical asymptote at x = 0.
MATA30F page 6
5. [5 marks] Given some numbers a and b, dene f : R R by
f(x) =
sin(17x)
sin(x)
if x < 0 ,
ax + b if 0 x 1 ,
ln(x) if x > 1 ,
Find a and b so that f is continuous on (/2, ). Fully justify your answers.
Solution:
Since sin 17x, sin x are both continuous for all x R and sin x = 0 for x = k for
k Z. Then
sin(17x)
sin(x)
is continuous on
2
, 0
.
Since ax + b is a polynomial then it is continuous on (0, 1).
Also, ln x is continuous on (0, ) therefore it is continuous on (1, ).
For f to be continuous at x = 0 we need
lim
x0
f(x) = lim
x0
+
f(x) = f(0).
So
lim
x0
f(x) = lim
x0
sin(17x)
sin(x)
= lim
x0
sin(17x)
17x
x
sin x
17x
x
= lim
x0
sin(17x)
17x
lim
x0
x
sin(x)
lim
x0
17)
1
= 1 1 17 lim
0
sin
= 1
= 17
lim
x0
+
f(x) = lim
x0
+
ax + b = b = f(0)
For continuity at 0 we need b = 17.
For continuity at 1 we need
lim
x1
f(x) = lim
x1
+
f(x) = f(1).
lim
x1
f(x) = lim
x1
ax + b = a + b = a + 17 = f(1)
lim
x1
+
f(x) = lim
x1
+
ln(x) = ln(1) = 0
For continuity at 1 we need a + 17 = 0 or a = 17.
Thus, if a = 17 and b = 17, then f is continuous on (/2, ).
MATA30F page 7
6. [10 marks] Determine if there is a solution to
x
5/3
+ x
2/3
+ 6 = 0 .
Justify your answer and give the full statement of the theorem you used.
Solution: Since the function f(x) = x
5/3
+x
2/3
+6 is the sum of powers of root functions
that are continuous on R, then f is continuous on R.
f(0) = 6 > 0 and
f(8) = (8)
5/3
+ (8)
2/3
+ 6
= (
3
8)
5
+ (
3
8)
2
+ 6
= (2)
5
+ (2)
2
+ 6
= 32 + 4 + 6 = 22 < 0
We have that f(8) < 0 < f(0) and since f is continuous on [8, 0], then by the
Intermediate Value Theorem there is some c (8, 0) such that f(c) = 0.
Thus there is at least one solution to x
5/3
+ x
2/3
+ 6 = 0 in (8, 0).
The Intermediate Value Theorem: If f is continuous on [a, b] and w is between f(a)
and f(b), then there is some c (a, b) such that f(c) = w.
MATA30F page 8
7. (a) [5 marks] Let f(x) =
1
x 2
. Use the denition of the derivative to nd f
(x).
Solution:
lim
h0
f(x + h) f(x)
h
= lim
h0
1
x+h2
1
x2
h
= lim
h0
1
x+h2
1
x2
h
= lim
h0
(x2)(x+h2)
(x2)(x+h2)
h
= lim
h0
h
(x 2)(x + h 2)h
= lim
h0
1
(x 2)(x + h 2)
=
1
(x 2)
2
(b) [5 marks] Find the line tangent line to the graph of f(x) =
1
x 2
at the point
(4, 1/2).
Solution:
Since f(4) =
1
4 2
=
1
2
, then the point (4, 1/2) is on the graph of f.
The slope of the tangent line at (4, 1/2) is m = f
(4) =
1
(4 2)
2
=
1
4
.
Thus:
1
4
=
y
1
2
x 4
Thus, the equation of the tangent line is y =
1
2
1
4
(x 4) =
1
4
x +
3
2
.
MATA30F page 9
8. [5 marks each; 25 marks] For the following given functions use dierentiation rules
to nd their required derivatives. Do not simplify.
(a) [5 marks] f(x) = e
x
(1 + sec x). Find f
(x).
Solution: Using the product rule and the chain rule:
f
(x) = e
x
(1 + sec x) + e
x
sec xtan x
(b) [5 marks] g(x) =
arcsin(x)
1 x
2
. Find g
(x).
Solution:
g
(x) =
1
1x
2
1 x
2
arcsin x
1
2
1x
2
(2x)
(
1 x
2
)
2
=
1x
2
1x
2
+
xarcsin x
1x
2
1 x
2
=
1x
2
+xarcsin x
1x
2
1 x
2
=
1 x
2
+ xarcsin x
1 x
2
(1 x
2
)
=
1 x
2
+ xarcsin x
(1 x
2
)
3/2
(c) [5 marks] g(x) = 2 sin(ln(x)) cos(ln(x)). Find g(x).
Solution: Using the product rule and the chain rule:
g
(x) = 2 cos(ln(x))
1
x
1
x
.
g
(x) =
2
x
[cos
2
(ln(x)) sin
2
(ln(x))] =
2
x
cos(2 lnx).
Or using the double angle identity sin 2y = 2 sin y cos y we get that g(x) =
2 sin(ln(x)) cos(ln(x)) = sin(2 lnx), thus
g
= 2(tanx)(sec
2
x) ln(x + 1) + tan
2
x
1
(x + 1)
Thus:
y = y
2(tanx)(sec
2
x) ln(x + 1) +
tan
2
x
(x + 1)
= (x + 1)
tan
2
x
2(tanx)(sec
2
x) ln(x + 1) +
tan
2
x
(x + 1)
(e) [5 marks] If e
xy
= e
4x
e
5y
, nd
dy
dx
.
Solution: Using implicit dierentiation on e
xy
= e
4x
e
5y
, we get:
e
xy
(y + xy
) = e
4x
4 e
5y
5y
.
Isolating all terms with y
e
xy
= e
4x
4 e
5y
5y
.
xy
e
xy
+ e
5y
5y
= 4e
4x
ye
xy
y
(xe
xy
+ 5e
5y
) = 4e
4x
ye
xy
Finally:
y
=
4e
4x
ye
xy
xe
xy
+ 5e
5y
MATA30F page 11
This page is intentionally blank.
MATA30F page 12
This page is intentionally blank.